2018
DOI: 10.1111/mec.14942
|View full text |Cite
|
Sign up to set email alerts
|

Putatively adaptive genetic variation in the giant California sea cucumber (Parastichopus californicus) as revealed by environmental association analysis of restriction‐site associated DNA sequencing data

Abstract: Understanding the spatial scale of local adaptation and the factors associated with adaptive diversity are important objectives for ecology and evolutionary biology, and have significant implications for effective conservation and management of wild populations and natural resources. In this study, we used an environmental association analysis to identify important bioclimatic variables correlated with putatively adaptive genetic variation in a benthic marine invertebrate-the giant California sea cucumber (Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(81 citation statements)
references
References 80 publications
7
72
0
Order By: Relevance
“…To date, empirical work focusing on the contribution of genomic background (e.g., standing genetic variation and chromosomal rearrangement) to adaptive variation in the presence of high gene flow have been limited to a restricted number of study systems (e.g., Tine et al 2014, Bernatchez 2016, Le Moan et al 2019, Barth et al 2017, Petterson et al 2019. Marine organisms are excellent biological models to address this issue since many marine species experience highly heterogeneous marine conditions potentially acting as selective agents, yet displaying very weak genetic differentiation due to large ܰ and high connectivity associated with strong dispersal capacities (Palumbi 1992, Bradbury et al 2008, Selkoe et al 2016, Xuereb et al 2018. Capelin (Mallotus villosus) is a key-forage fish species (Buren et al 2014) that display such characteristics typical of marine organisms.…”
Section: Introductionmentioning
confidence: 99%
“…To date, empirical work focusing on the contribution of genomic background (e.g., standing genetic variation and chromosomal rearrangement) to adaptive variation in the presence of high gene flow have been limited to a restricted number of study systems (e.g., Tine et al 2014, Bernatchez 2016, Le Moan et al 2019, Barth et al 2017, Petterson et al 2019. Marine organisms are excellent biological models to address this issue since many marine species experience highly heterogeneous marine conditions potentially acting as selective agents, yet displaying very weak genetic differentiation due to large ܰ and high connectivity associated with strong dispersal capacities (Palumbi 1992, Bradbury et al 2008, Selkoe et al 2016, Xuereb et al 2018. Capelin (Mallotus villosus) is a key-forage fish species (Buren et al 2014) that display such characteristics typical of marine organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Salinity emerging as a major selective force on C. punctatus is understandable, as this species is an osmoconformer that inhabits estuarine environments [64], and because the larval development of decapods is in uenced by changes in salinity [65]. The lack of clear correlations with any environmental variables is unexpected for the urchin P. angulosus, given that previous studies have shown genomic variation corresponding to SST gradients in other echinoderms [28,66]. Additionally, the paucity of annotated genomes for marine invertebrates makes it di cult to identify the functionality of outlier loci, which likely led to the limited number of BLAST hits for the 2X outliers in each species (Additional File 4).…”
Section: Different Environmental Drivers Of Selection Across Speciesmentioning
confidence: 99%
“…3). Previous seascape genomic studies in temperate regions have frequently identi ed some measure of SST as the best predictor of genomic variation of marine invertebrates [9,11,12,25,28,63], which is most likely due to SST affecting both cellular processes, and life-history events such as spawning and larval development [59]. However, for P. angulosus, Trange and SSTmean best explained genomic variation, whereas SSSmean best explained the structure of C. punctatus.…”
Section: Different Environmental Drivers Of Selection Across Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a recent genomic study on the summer flounder Paralichthys dentatus found very weak spatial genetic structuring and identified loci whose allele frequency distribution was concordant with temperaturesuggesting adaptive genetic diversity driven by temperature (Hoey & Pinsky, 2018). Similarly, temperature is also suggested to be a driver of adaptive diversity in sea cucumber Parastichopus californicus after statistically controlling for population structuring (Xuereb et al, 2018). With the increasing human-mediated threats to marine biodiversity Urban, 2015), understanding adaptive evolutionary processes is becoming more timely, especially in tropical marine systems that are predicted to be highly impacted by changes in climatic conditions (Molinos et al, 2016).…”
Section: Introductionmentioning
confidence: 99%